A STUDY ON THE USE OF WARM-UP ACTIVITIES TO MOTIVATE GRADE 10 STUDENTS IN ENGLISH LESSONS AT NGOC TAO HIGH SCHOOL - Đỗ, Thị An (2021)
The research is undertaken to find out the ways to get students' attention at the beginning of the class by means of enjoyable and short activities as well as to adapt these activities successfully in teaching process. The specific objectives of the study are: To point out the roles of WAs as perceived by Grade 10 students. To identify the kinds of WAs which effectively motivate students The aim of the study is also specified in the research questions below